Communication and the globalization of culture : beyond tradition and borders - Mohammed, S. Nick, 1968- (Rowman & Littlefield Pub. Group, 2011)
Shaheed Nick Mohammed's Communication and the Globalization of Culture: Beyond Tradition and Borders provides a unique perspective on the concept of culture and its fate in the globalized, mediated environment. Acknowledging widespread fears of cultural erosion at the hands of dominant global forces, Mohammed argues that what we understand as culture has always been the product of global forces, including those of trade and exchange. Our very conceptions of culture are questioned. The sanctity of tradition, religion, and heritage, the book suggests, should give way to an appreciation of the qu.